2019
DOI: 10.1021/acs.inorgchem.9b00632
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Counteranion on the Zero-Field Splitting of Tetrahedral Cobalt(II) Thiourea Complexes

Abstract: Four mononuclear cobalt­(II) complexes with pseudo tetrahedral geometry were isolated with different counteranions; their structure solution reveals the molecular formula as [Co­(L1)4]­X2 [where L1 = thiourea (NH2CSNH2) and X = NO3 (1), Br (2), and I (3)] and [Co­(L1)4]­(SiF6) (4). The detailed analysis of direct-current (dc) magnetic data reveals a zero-field splitting (ZFS; D) with m S = ±3/2 as the ground levels (D < 0) for the four complexes. The magnitude of the ZFS parameter is larger, in absolute value,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 76 publications
(140 reference statements)
1
30
0
Order By: Relevance
“…It has been shown on several occasions that four-coordinate Co(II) complexes in distorted tetrahedral geometries exhibit very high negative D-values, and some explanations have been presented by us and others (Zadrozny et al, 2013;Zadrozny & Long, 2011;Tripathi et al, 2019;Vaidya et al, 2018Vaidya et al, , 2016Vaidya et al, , 2014Rechkemmer et al, 2016;Damgaard-Møller et al, 2020c). In the current work, we combine results from neutron and synchrotron diffraction to provide irrefutable experimental evidence for the origin of this behavior.…”
Section: Introductionmentioning
confidence: 54%
“…It has been shown on several occasions that four-coordinate Co(II) complexes in distorted tetrahedral geometries exhibit very high negative D-values, and some explanations have been presented by us and others (Zadrozny et al, 2013;Zadrozny & Long, 2011;Tripathi et al, 2019;Vaidya et al, 2018Vaidya et al, , 2016Vaidya et al, , 2014Rechkemmer et al, 2016;Damgaard-Møller et al, 2020c). In the current work, we combine results from neutron and synchrotron diffraction to provide irrefutable experimental evidence for the origin of this behavior.…”
Section: Introductionmentioning
confidence: 54%
“…on this complex predicted a very large negative D value of −70 cm −1 [9a] . Magneto‐structural correlations performed on this type of {CoS 4 } system by us and others further revealed that the magnetic anisotropy of these complexes is controlled by the following factors: i) structural parameters such as bond angle and torsional angle around the first and second coordination sphere atoms, [12c, 39] ii) effect of donor atoms or ligand field strength, [39b, 40] iii) spin‐orbit coupling of the donor atoms [41] and also iv) counterions [39d, 42] . Soft donor groups such as S, Se/Br, I coordination bring down the 4 A 2 → 4 T 2 (ligand field states in T d symmetry) transition energy gap, and thus the D switches to negative from positive.…”
Section: Zero‐field Splitting In Transition Metal‐based Simsmentioning
confidence: 75%
“…A nearly degenerate (dx2-y2,bolddxy) orbital pair was obtained for 2’ , with ΔE =20.8 cm −1 and D =−155 cm −1 . In order to further validate our hypothesis on a larger population of compounds, we performed similar calculations for additional 19 [CoE 4 ] structures (with E=O, N, S, Se) available from the CSD database (Sections S4 and S5) [17–19,22,25,31,42] . They hold different ligand types and allow to cover a broader range of E−Co−E angles from 66 to 107°.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, 3d based systems are still arousing interest because of their highly‐tunable properties, contrary to lanthanide‐containing compounds [11,12] . In the past decade, remarkable 3d mononuclear SMMs were synthesized, [13] including two‐coordinate iron [14] and cobalt [15] systems, as well as highly distorted tetrahedral cobalt complexes [16–22] . Common to all these compounds is that the ligand field distortions recreate the OAM [15] giving a large spin‐orbit coupling (SOC) and therefore large zero‐field splitting (ZFS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation